A wrinkle in time [videorecording (Blu-Ray + DVD)] - Lee, Jennifer (Screenwriter); Stockwell, Jeff; Winfrey, Oprah; Witherspoon, Reese, 1976-; Kaling, Mindy; Reid, Storm, 2003-; Miller, Levi, 2002-; McCabe, Deric, 2008-; Mbatha-Raw, Gugu, 1983-; Peña, Michael, 1976-; Galifianakis, Zach; Pine, Chris, 1980-; et al. (Disney Blu-ray., 2018)
After the disappearance of her scientist father, three peculiar beings send Meg, her brother, and her friend to space in order to find him.